Indikator yang Membedakan Gejala Psikotik dengan Pengalaman Spiritual dalam Perspektif Neurosains (Neuro-Anatomi) - Lumingkewas, Priscilla E.; Pasiak, Taufiq F.; Ticoalu, Shane H.R. (Universitas Sam Ratulangi, 2017)
Abstract: Psychotic disorder is a mental disorder characterized by hallucinations, delusions, catatonic behavior, chaotic behavior, chaotic speaking and are generally accompanied by poor performance. Spirituality is a belief related to the Almighty and the Creator. Current neuroscience approaches have touched the spiritual dimension, well-known as spiritual neuroscience. This term is used to describe human spirituality in terms of health and medicine perspectives. People with advanced spiritual personality are often regarded as those who have mental illness by the people around them. This study was aimed to determine the difference between psychotic symptoms and spiritual experience in the perspective of neuroscience. This was a descriptive study with a retrospective approach. We used research articles in journals pertaining to psychotic symptoms, spiritual experiences, and neuroscience, in addition searching for indicators that could help to differentiate the psychotic symptoms and spiritual experiences using a systematic review technique. Conclusion: There is a difference in brain activity between people who had spiritual experiences and those with psychotic symptoms.Keywords: neuroscience, spiritual, psychoticÂ Abstrak: Gangguan psikotik adalah gangguan jiwa yang ditandai dengan adanya halusinasi, waham, perilaku kataton, perilaku kacau, pembicaraan kacau yang pada umumnya disertai tilikan yang buruk. Spiritualitas merupakan keyakinan yang berkaitan dengan Yang Maha Kuasa dan Maha Pencipta. Saat ini pendekatan neurosains telah menyentuh dimensi spiritual, yang lebih dikenal dengan istilah neurosains spiritual. Istilah ini dipakai untuk menjelaskan spiritualitas manusia dipandang dari sisi perspektif kesehatan dan kedokteran. Orang dengan kepribadian spiritual yang maju sering dianggap memiliki penyakit mental oleh orang-orang di sekitarnya. Penelitian ini bertujuan untuk mengetahui perbedaan antara gejala psikotik dengan pengalaman spiritual dalam perspektif neurosains. Jenis penelitian ialah deskriptif retrospektif dengan cara mempelajari penelitian-penelitian yang telah dimuat dalam jurnal-jurnal yang membahas tentang gejala psikotik, pengalaman spiritual, dan neurosains serta mencari indikator yang dapat membedakan, dengan teknik telaah sistematik. Simpulan: Terdapat perbedaan aktivitas otak pada orang yang sementara mengalami pengalaman spiritual dengan orang yang mengalami gejala psikotik.Kata kunci: neurosains, spiritual, psikotik